ØªØ·ÙˆÙŠØ± Ù…Ù†Ù‡Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Musthafa, Izzudin (Jurnal Pendidikan Islam, 2016)
This study is based on the reality that learning process of Arabic in UIN Sunan Gunung Djati Bandung has not been able to reach the expected result. It is indicated in the result of language proficiency test of the students who learn Arabic in a number of departments and programs in UIN SGD Bandung. Therefore, it is necessary that appropriate model of curriculum be found as a solution to improve the quality of the graduates in mastery Arabic skills; that is, the curriculum for teaching learning Arabic that facilitates students to achieve the goals, content standard, teaching learning process, and evaluation system. This study utilizes Research and Development method, since it focuses on curriculum development of Arabic in UIN SGD Bandung.